Physicochemical Controls on Zones of Higher Coral Stress Where Black Band Disease Occurs at Mākua Reef, Kaua‘i, Hawai‘i - Oberle, Ferdinand K. J.; Storlazzi, Curt D.; Cheriton, Olivia M.; Takesue, Renee K.; Hoover, Daniel J.; Logan, Joshua B.; Runyon, Christina; Kellogg, Christina A.; Johnson, Cordell D.; Swarzenski, Peter W. (Frontiers in Marine Science, 2019)
Pervasive and sustained coral diseases contribute to the systemic degradation of reef ecosystems, however, to date an understanding of the physicochemical controls on a coral disease event is still largely lacking. Water circulation and residence times and submarine groundwater discharge all determine the degree to which reef organisms are exposed to the variable chemistry of overlying waters; understanding these physical controls is thus necessary to interpret spatial patterns in coral health. The recent discovery of coral Black Band Disease at Mākua Reef on Kauaʻi, Hawaiʻi prompted an investigation into the physicochemical drivers and geomorphic controls of reef water circulation, and the temporally variable nutrient fluxes derived from submarine groundwater discharge. Results reveal localized stagnant water parcels at Mākua Reef where groundwater-derived high nutrient loading and low salinities act in concert as stressors to coralline health – and where Black Band Disease was uniquely identified. The observed high nutrient levels during low tide conditions are likely associated with nearby upstream cesspools and drain fields. Information obtained using such a multidisciplinary approach has direct value for successful management of coastal aquifers and the health and sustainability of adjacent nearshore coral reef ecosystems.